Perspektif Masyarakat Pengguna Jalan Atas Ojek Online: Sudut Pandang Kemacetan - Dalimunthe, Ibram Pinondang; Nofryanti, Nofryanti (Media Ekonomi, 2020)
This study provides an overview and analysis of the perceptions of road users on online motorcycle taxi behavior from the point of view of congestion. The research method uses a descriptive quantitative approach that explains the research objectives. The population of this study is all road users in the Jakarta, Bogor, Depok, Tangerang and Bekasi areas. The samples used for research are people who have used online motorcycle taxi service facilities, as well as the general public who have views regarding online transportation. Data collection techniques using a questionnaire and distributed to respondents. The results showed that people's perceptions of online motorcycle taxis were able to create safety and comfort for customers, facilitate delivery of goods, be able to take the initiative to find alternative ways to shorten mileage, and affordable online ojek costs for customers. However, on the other hand, respondents said that the existence of online motorcycle taxis can contribute to the level of congestion on the road, respondents agreed that a special shelter should be made for customers and online motorcycle taxi drivers while waiting for orders so as not to interfere with the activities of other road users that have an impact on congestion.